Legal Discourse on Customary Forest Determination Progressive Law Based - Candra Perbawati; Malicia Evendia; Ade Arif Firmansyah; Yulia Neta (Universitas Lampung, 2023)
Customary forests are an integral part of the life of indigenous and tribal peoples. MK Decision No. 35/PUU-X/2012 is a progressive step stipulating that customary forests are no longer part of State forests. However, after the decision, there is still a long process that the Indigenous Peoples must pass to obtain their rights. This article aims to describe the legal discourse in determining the customary forest. Using doctrinal research methods as well as statutory and conceptual approaches, it was found that: The designation of customary forests is an important matter in the context of implementing the constitutional rights of customary law communities that existed even before Indonesia was established as a sovereign country. The long and procedural process of establishing customary forests requires the support of the regional government through various progressive policies to create indigenous peoples who are sovereign over their customary forests. With the legal credo for humans, progressive law offers an approach that can become the basis for the realization of legal policies for establishing customary forests in the regions.